Correlations between gut microbiota community structures of Tibetans and geography. Issue 1 (December 2017) - Lan, Daoliang; Ji, Wenhui; Lin, Baoshan; Chen, Yabing; Huang, Cai; Xiong, Xianrong; Fu, Mei; Mipam, Tserang; Ai, Yi; Zeng, Bo; Li, Ying; Cai, Zhixin; et al.
Abstract Microbial communities of human gut directly influence health and bear adaptive potential to different geography environment and lifestyles. However, knowledge about the influences of altitude and geography on the gut microbiota of Tibetans is currently limited. In this study, fecal microbiota from 208 Tibetans across six different locations were analyzed by MiSeq sequencing; these locations included Gannan, Gangcha, Tianzhu, Hongyuan, Lhasa and Nagqu, with altitudes above sea level ranging from 2800 m to 4500 m across the Tibetan plateau. Significant differences were observed in microbial diversity and richness in different locations. At the phylum level, gut populations of Tibetans comprised Bacteroidetes (60.00%), Firmicutes (29.04%), Proteobacteria (5.40%), and Actinobacteria (3.85%) and were marked by a low ratio (0.48) of Firmicutes to Bacteroidetes. Analysis based on operational taxonomic unit level revealed that core microbiotas includedPrevotella, Faecalibacterium, andBlautia, whereasPrevotella predominated all locations, except Gangcha. Four community state types were detected in all samples, and they mainly belong toPrevotella, Bacteroides, andRuminococcaceae . Principal component analysis and related correspondence analysis results revealed that bacterial profiles in Tibetan guts varied significantly with increasing altitude, BMI, and age, and facultative anaerobes were rich in Tibetan guts. Gut microbiota may play important roles in regulating high-altitude and geographical adaptations.